DIFFERENTIATED INSTRUCTION IN MIXED-ABILITY ENGLISH CLASSES IN SECONDARY SCHOOL (World Bulletin of Education and Learning, 2025)
Differentiated instruction has become an essential pedagogical approach in modern secondary school education, particularly in mixed-ability English language classrooms where learners demonstrate significant differences in language proficiency, learning styles, motivation, and cognitive readiness. The relevance of differentiated instruction is especially pronounced in contexts where English is taught as a foreign language and where classrooms are characterized by heterogeneity in learners’ academic backgrounds and individual capacities. This article explores the theoretical foundations and practical significance of differentiated instruction in mixed-ability English classes at the secondary school level. The study emphasizes the role of differentiation in addressing individual learner needs while maintaining common educational standards and learning objectives. Particular attention is given to instructional strategies that enable teachers to adapt content, process, and learning outcomes without fragmenting the classroom community. The paper also considers the pedagogical challenges faced by English teachers in implementing differentiation and highlights the importance of teacher preparedness, reflective practice, and methodological flexibility. The findings underscore that differentiated instruction contributes to increased learner engagement, improved language achievement, and more inclusive classroom interaction, making it a critical component of effective English language teaching in contemporary secondary education.
Keywords: differentiated instruction, mixed-ability classes, English language teaching, learner diversity, secondary school